(untitled) (Polish Yearbook of International Law, 2018)
This article focuses on mobility of companies in the European Union in the light of the Court of Justice’s judgment in the C-106/16 Polbud – Wykonawstwo sp. z o.o. case. The Court of Justice has once again interpreted the treaty provisions relating to the EU freedom of establishment in the context of cross-border conversion of companies. The in-depth analysis of the case from the substantive law perspective as well as from the conflict-of-law perspective has raised some doubts with regard to the background of the judgment. Therefore, the article assesses whether the cross-border transfer of a seat took place in the Polbud case or the cross-border conversion, or possibly a new company has come into existence. Most of the analysis is aimed at exposing the risks related to the companies’ mobility under the rules adopted in the Polbud judgment, in particular in the absence of respective European and national regulation.